Personalized paroxysmal atrial fibrillation ablation by tailoring ablation index to the left atrial wall thickness: the 'Ablate by-LAW' single-centre study—a pilot study. Issue 3 (4th September 2021) - Teres, Cheryl; Soto-Iglesias, David; Penela, Diego; Jáuregui, Beatriz; Ordoñez, Augusto; Chauca, Alfredo; Carreño, Jose Miguel; Scherer, Claudia; San Antonio, Rodolfo; Huguet, Marina; Roque, Albert; Ramírez, Carlos; et al.
Abstract: Aims: To determine if adapting the ablation index (AI) to the left atrial wall thickness (LAWT), which is a determinant of lesion transmurality, is feasible, effective, and safe during paroxysmal atrial fibrillation (PAF) ablation. Methods and results: Consecutive patients referred for PAF first ablation. Left atrial wall thickness three-dimensional maps were obtained from multidetector computed tomography and integrated into the CARTO navigation system. Left atrial wall thickness was categorized into 1 mm layers and AI was titrated to the LAWT. The ablation line was personalized to avoid thicker regions. Primary endpoints were acute efficacy and safety, and freedom from atrial fibrillation (AF) recurrences. Follow-up (FU) was scheduled at 1, 3, 6, and every 6 months thereafter. Ninety patients [60 (67%) male, age 58 ± 13 years] were included. Mean LAWT was 1.25 ± 0.62 mm. Mean AI was 366 ± 26 on the right pulmonary veins with a first-pass isolation in 84 (93%) patients and 380 ± 42 on the left pulmonary veins with first-pass in 87 (97%). Procedure time was 59 min (49–66); radiofrequency (RF) time 14 min (12.5–16); and fluoroscopy time 0.7 min (0.5–1.4). No major complication occurred. Eighty-four out of 90 (93.3%) patients were free of recurrence after a mean FU of 16 ± 4 months. Conclusion: Personalized AF ablation, adapting the AI to LAWT allowed pulmonary vein isolation with low RF delivery, fluoroscopy, and procedure time while obtaining a high rate of first-pass isolation, in this patient population. Freedom from AF recurrences was as high as in more demanding ablation protocols. A multicentre trial is ongoing to evaluate reproducibility of these results. Graphical Abstract: